Math virtual assistant

About Snapxam Calculators Topics Go Premium
ENGESP
Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Solve the equation (2x-5)(x-3)-3(x-5)=x

\left(2x-5\right)\left(x-3\right)-3\left(x-5\right)=x

Step by step solution

Problem

$\left(2x-5\right)\left(x-3\right)-3\left(x-5\right)=x$

Show full step-by-step solution

Answer

$-x-3\left(x-5\right)+\left(x-3\right)\left(2x-5\right)=0$
$\left(2x-5\right)\left(x-3\right)-3\left(x-5\right)=x$

Main topic:

Equations

Used formulas:

0

Time to solve it:

0.24 seconds